Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s11356-015-4567-7
|View full text |Cite
|
Sign up to set email alerts
|

DEHP reduces thyroid hormones via interacting with hormone synthesis-related proteins, deiodinases, transthyretin, receptors, and hepatic enzymes in rats

Abstract: Di-(2-ethylhexyl) phthalate (DEHP) is used extensively in many personal care and consumer products, resulting in widespread nonoccupational human exposure through multiple routes and media. Limited studies suggest that exposure to DEHP may be associated with altered thyroid function, but detailed mechanisms are unclear. In order to elucidate potential mechanisms by which DEHP disturbs thyroid hormone homeostasis, Sprague-Dawley (SD) rats were dosed with DEHP by gavage at 0, 250, 500, and 750 mg/kg/day for 30 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
88
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(101 citation statements)
references
References 27 publications
5
88
1
Order By: Relevance
“…In the hypothalamus, the lowered circulating levels of T4 and T3 in the DEHP-treated rats may primarily be the consequence of thyroid toxicity, resulting in the increased TRH expression. These results, DEHP down-regulated the levels of THs and increased TRH expression in rats, are consistent with a previous study [20]. Another report that involved animal studies described that decreased the levels of serum T4 with prolonged DEHP exposure [21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the hypothalamus, the lowered circulating levels of T4 and T3 in the DEHP-treated rats may primarily be the consequence of thyroid toxicity, resulting in the increased TRH expression. These results, DEHP down-regulated the levels of THs and increased TRH expression in rats, are consistent with a previous study [20]. Another report that involved animal studies described that decreased the levels of serum T4 with prolonged DEHP exposure [21].…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have observed an inverse association between MEHP urinary concentrations and free T4 and T3 serum levels in men and similar negative correlations have been found in pregnant women [18,19]. In animal studies, rats and fishes fed with diets contaminated with DEHP were found to have thyroid alterations and lower plasma T4 concentrations [20,21]. But the detailed mechanisms that are involved in this process are unclear.…”
mentioning
confidence: 95%
“…However, no significant changes in D1 and D2 protein levels in the liver and hypothalamus were observed after triclosan exposure. Similar results were also found in other studies [22]. However, the study reported that D2 expression was downregulated in gargarizans embryos that were exposed to 60 and 150 µg/L triclosan [23].…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, limited in vitro studies have shown that phthalates may have thyroid hormone receptor antagonist activity (Shen et al 2009; Sugiyama et al 2005). Several studies have also demonstrated potential phthalate actions on thyroid hormone biosynthesis and biotransport (Breous et al 2005; Ishihara et al 2003; Liu et al 2015; Wenzel et al 2005; Zhai et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Animal and in vitro studies suggest that phthalates may be capable of disrupting circulating thyroid hormone levels, although the exact biological mechanism(s) of action remain unclear (Boas et al 2012; Liu et al 2015; Zhai et al 2014). Additionally, a limited number of epidemiological studies have shown that phthalates may alter thyroid hormone levels in adult men and nonpregnant women as well as children (Boas et al 2010; Meeker et al 2007; Meeker and Ferguson 2011).…”
Section: Introductionmentioning
confidence: 99%